Application of Ultrasound on the Extraction of Vitexin from Ficus Deltoidea Leaves - Nur Aimi Syairah , Mohd Abdul Alim; Ahmad Ziad, Sulaiman; Azilah, Ajit (Asian Research Publishing Network (ARPN), 2016)
Ficus deltoidea or Mas cotek is one of the most popular plant herbs that have been widely used traditionally as postpartum treatment and health tonic. Preliminary or existing extraction method has been used to extract the plant herbs that have low productivity range. This method however can still produce the desired products, but the work can be laborious and not efficient in large scale processing. Besides, the sample preparation has no evidence in advances because obtaining such extraction products at sufficient concentrations usually involves extraction with large amounts of organic solvents and toxic, followed by evaporation. Production of Vitexin from Ficus deltoidea extraction under various sonication regiments is reported. Batch extractions were carried at low intensity sonication (8.66 W cm-2 sonication intensity at the sonotrode tip) using 10%, 20% and 40% duty cycles. (A duty cycle of 10%, for example, was equivalent to sonication for 1 s followed by a rest period (no sonication) of 10 s.) The extracts were compared with those obtained by conventional boiling extraction, in terms of bioactive constituents yield and chemical composition. In the aqueous (conventional) extracts, the actual percentage weight of Vitexin varied in the range 0.122 ± 0.013 ~ 0.386 ± 0.018 (%w/w) compared to sonicated extracts with 2-fold increases at a range of 0.127 ± 0.001 ~ 0.738 ± 0.050 (%w/w) after 8 hours of extraction with sample-to-water ratio of 10:1 (g/ml) at 50, 70 and 100°C. Both ultrasonic-assisted and aqueous extracts were characterized and standardized by HPLC-diode array detector using a pharmacologically active marker, Vitexin. The experimental values under optimal conditions were in good consistent with the predicted values, which suggested that ultrasonic-assisted extraction (UAE) is more efficient process as compared to conventional boiling extraction (AE). It recommends that ultrasound extraction of F. deltoidea leaves is substantially feasible to replace the traditional timeconsuming and low efficiency preparation procedure in the future modernized and commercialized manufacture of this highly valuable herbal medicine.